BOOK TAX DIFFERENCES, OPERATING CASH FLOW, LEVELS OF DEBT, AND PERSISTENCE OF EARNINGS - Nurdina Nurdina; R Yudi Sidharta; Soffia Pudji Estiasih; Salsabila Abidah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
One part of the report that gets a lot of attention from internal and external parties of the company is information about profits. Quality profit information will help interested parties in policy making. This study aims to analyze the role of book tax differences, operating cash flow, and debt levels on earnings persistence. The research population is manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange for the 2018-2020 period, totaling 51 companies. The sample in this study amounted to 14 manufacturing companies in the consumer goods industry sector using a purposive sampling technique. The results in this study indicate that book tax differences affect earnings persistence, operating cash flow does not affect earnings persistence, and debt levels do not affect earnings persistence in manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange.